Development and Performance Evaluation of a Low-Cost In-House rRTPCR Assay in Ecuador for the Detection of SARS-CoV-2 - Salinas-Pinta, Marco; Aguirre, Diana; Torre, David De la; Pérez-Galarza, Jorge; Pibaque, Ronny; Beltran, Paul; Veloz, Tatiana; Baldeón-Rojas, Lucy (Archives of Clinical and Biomedical Research, 2023)
Background: Ecuador has had the greatest fatality rate from Coronavirus (COVID-19) in South America during the SARS-CoV-2 pandemic. To control the pandemic, it is necessary to test as much population as possible to prevent the spread of the SARS-CoV-2 infection. For the Ecuadorian population, accessing a PCR test is challenging, since commercial screening kits tend to be expensive. Aim: The objective of this study was to develop an in-house duplex rRTPCR protocol for the detection of SARS-CoV-2 that contributes to the screening while keeping quality and low testing costs. Results: An in-house duplex rRT-PCR protocol based on the viral envelope (E) gene target of SARS-CoV-2 and human ribonuclease P gene (RP) as an internal control is reported. The protocol was optimized to obtain with the primers E an efficiency of up to 94.45% and detection of 100% of SARSCoV- 2 up to 15 copies per uL. The clinical performance was determined by a sensibility of 93.8% and specificity of 98.3%. Conclusion: We developed, standardized, and validated a low-cost, sensitive in-house duplex rRT-PCR assay that may be utilized in lowincome countries.